The Impact of School-Based Smartphone Addiction Education Programs on High School Students - Isneini, Isneini; Elvin, Said Devi; Jauhari, Julianti (Journal Keperawatan, 2025)
Background: Smartphone addiction is increasing among adolescents and has the potential to lead to various psychological disorders such as depression, anxiety, stress, and low self-esteem. Excessive smartphone use can also disrupt students' concentration in learning, the quality of their social relationships, and their emotional balance. Planned and sustained prevention efforts are needed to minimize the negative impacts of smartphone use on adolescents. In this regard, the school environment plays a very strategic role as a platform for education, character development, and the prevention of addictive behavior towards digital technology. Purpose: To determine the effect of school-based intervention programs in reducing levels of addiction, stress, anxiety, and depression in senior high school students in Banda Aceh City. Methods: The study used a quasi-experimental design with a control group. The sample size was determined through a power analysis with a medium effect size, power of 0.80, a 95% confidence level, and an alpha of 0.05. This resulted in 128 respondents, consisting of 64 students in the intervention group and 64 students in the control group, who were randomly selected. The study location was selected using cluster random sampling. The intervention, a school-based smartphone addiction prevention program, was implemented in four 50-minute sessions. The instruments used included the Korean Smartphone Addiction Proneness Scale (K-SAPS) to assess smartphone addiction and the Depression Anxiety Stress Scale (DASS-21) to assess psychosocial status. Results: There were significant differences between the intervention and control groups on the variables of smartphone addiction (p = 0.000), stress (p = 0.015), anxiety (p = 0.048), depression (p = 0.009), self-esteem (p = 0.000), and emotional status (p = 0.002) after the intervention. Conclusion: School-based smartphone addiction prevention programs have been shown to be effective in reducing levels of addiction, stress, anxiety, and depression, as well as increasing self-esteem and emotional stability in high school students